Knowledge management as a tool for improving business processes: an action research approach - Martínez-Martínez, Aurora; Cerdá Suárez, Luis Manuel; Sánchez Montero, Roberto; Asensio del Arco, Eva (Journal of Industrial Engineering and Management, 2018)
Purpose: The aim of this study is to investigate the importance of Knowledge Management as a tool for improving business processes in a different context from the industrial organizations, as an archaeological museum. Design/methodology/approach: Using data collected from the National Museum of the Sultanate of Oman in Muscat, a methodology for analysis and improvement of processes (the Business Cycle Management Process, CMP) is designed and validated. This application is described as an eight phases process based on Six Sigma DMAIC. The model has a characteristic "P" shape. Findings: As the results obtained by the process improvement initiative show, we highlight the relevance of the improvement in all aspects regarding the security in showcases in that context. Research limitations/implications: The complexity of implementing indicators and the partial vision of the project as data were only obtained from a part of one of the companies involved in the construction of the museum. An important implication of this paper is in order to present a methodology to improve the museum processes focusing on the reduction of errors and also adding value for the visitors. Practical implications: The relevance to intervene on certain relevant variables at different levels of management performance is verified. Social implications: Improving the quality of leisure services in order to the identification of certain challenges regarding the nature and competitiveness of cultural services. Originality/value: The current work has served as a repository of knowledge applicable to new similar projects, in which to take into account the peculiarities of each case and in particular the level of quality demanded by the client in a cultural context. It is important to take into account the degree of avoidable dissatisfaction (number of solvable problems that would lead to dissatisfaction), the opportunity for improvement, the reduction of operational waste and the need for coordination.
Keywords: knowledge management; business processes; improvement; security; museum; Scopus; Emerging